ANALYSIS OF THE EFFECT OF PERSONAL FINANCIAL NEED, CORPORATE GOVERNANCE, ECONOMIC INSTABILITY AND FINANCIAL TARGETS ON POTENTIAL FINANCIAL SHENANIGANS RISKS - Trisandi Eka Putri; Inna Mustika Sani; Siti Nur Farahin Binti Baharum; Asep Kurniawan (ZILLZELL MEDIA PRIMA, 2024)
Financial report are a form of communication between companies and stakeholders. Financial shenanigans are action that deliberately damage the reported financial performance and financial condition of a company. This research uses secondary data with quantitative methods, with the type of data in the form of company documents, namely financial reports, balance sheets and profit and los reports for retail sector companies listed on the Indonesia Stock Exchange and the Malaysia Stock Exchange. The sample research method used was purposive sampling. Personal financial need has a positive effect on the potential risk of financial shenanigans, corporate governance and financial target has a negative effect on the potential risk of financial shenanigans, and economic instability has not effect on the potential risk of financial shenanigans. Future research are expected to be able to use different research methodes from previous research, with the aim of finding out how the independent variable influences the dependent variable.